PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI PUSAT PENGEMBANGAN DAN PEMBERDAYAAN PENDIDIK DAN TENAGA KEPENDIDIKAN IPA BANDUNG - Ade Resma Nuraeni (Universitas Pendidikan Indonesia, 2021)
The research entitled “The Effect of Work Discipline on Employee Performance at the Center for the Development and Empowerment of Science Educators and Education Personnel (P4TK IPA) Bandung”, is a study that focuses on the description of work discipline, and employee performance. Work discipline is one of the most important factors in human resource management. Human resources as one of the resources in the organization have an important role and responsibility in achieving organizational goals. Based on this, this study was conducted to determine the level of employee discipline, employee performance, and the effect of work discipline on performance of widyaiswara employees at PPPPTK IPA. This study uses a descriptive verification method with a quantitative approach accompanied by a literature study. Data collection techniques is using questionnaires distributed to 46 widyaiswara employees at PPPPTK IPA. Findings from the calculations through non-parametric statistical techniques and Spearman Rank Correlation methods, indicating that the relationship between the two variables based on the value of the correlation coefficient on the X variable (Work Discipline) and Y variable (Employee Performance) is closeness with moderate category with a positive and significant relationship. Thus, it can be said that the X variable (Work Discipline) has a positive and significant effect on the Y variable (Employee Performance). Based on the result, it is hoped that the Head of the PPPPTK IPA Center, as the party assessing of employee performance, can pay more attention to and act decisively on employee discipline. Because discipline is an important factor that affects the employee performance, so with the high work discipline, and good employee performance, will help achieve more optimal organizational goals.